Sentence Writing Skills Through Picture and Picture Learning Model: Keterampilan Menulis Kalimat Melalui Model Pembelajaran Gambar dan Gambar - Andika Saputra; Apdoludin; Reni Guswita (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Writing is a fundamental language skill that plays a crucial role in developing students’ critical and logical thinking. Specific Background: However, elementary school students often struggle with constructing coherent sentences due to limited vocabulary, lack of structural understanding, and low motivation in writing activities. Knowledge Gap: Previous studies on the Picture and Picture model mainly focused on reading comprehension, with limited exploration of its application in sentence writing, especially within the context of the Kurikulum Merdeka. Aims: This study aims to improve fourth-grade students’ sentence writing skills through the systematic application of the Picture and Picture learning model. Results: Conducted as a classroom action research in two cycles with 25 participants, the findings revealed significant improvements: teacher performance increased from 76.19% to 90.48%, student active participation rose from 24% to 44%, and sentence writing mastery improved from 68% to 84%. Novelty: The novelty lies in integrating the Picture and Picture model with the Kurikulum Merdeka, focusing on visual-based sentence construction in Bahasa Indonesia learning. Implications: These results suggest that Picture and Picture can serve as an effective pedagogical strategy to foster creativity, independence, and linguistic competence in primary education.Highlight : The Picture and Picture model improves sentence writing skills. Students become more active and participative. Learning outcomes increase from Cycle I to Cycle II. Keywords : Sentence Writing Skills, Picture And Picture Model, Elementary School, Classroom Action Research, Indonesian Language